Students' Perceptions of a Compulsory Guidance Program - Yee, Dianne; Pawlovitch, Walter (Canadian Journal of Counselling and Psychotherapy, 2011)
This descriptive study investigates students' perceptions of the primary compulsory segment of the career guidance program offered by Swift Current Comprehensive High School (SCCHS). Data was gathered to examine the perceived effectiveness of the Strong-Campbell Interest Inventory (SCII) component, of the Differential Aptitude Tests (DAT) component, of the CHOICES component, and of the total program. The population of students (243) who completed the program responded to a questionnaire, the Pathways Effectiveness Survey, which was developed by the researchers. A random sample of 15 boys and 15 girls were then interviewed. A structured interview, the Pathways Interview, was also designed by the researchers. Students reported positive perceptions of the total program and of counsellor assistance. The CHOICES component of the program was perceived most positively, while students reported mixed perceptions of the SCII and DAT components of the program. Regular Core students generally perceived the program to be more beneficial than Alternate Modified students. Girls were consistently more positive about the program than were boys.